OBTAIN OF ALCOHOL FROM RICE BRAN - Bautista C., Mario (2005)
This work describes a technologycal process to obtain alcohol from rice bran.The optimum time of fermentation was 12 hours with a yield production of 57% based on starch contents in the rice bran.